Associations between depression, sleep disturbance, and apolipoprotein E in the development of Alzheimer's disease: dementia. (29th March 2016) - Burke, Shanna L.; Maramaldi, Peter; Cadet, Tamara; Kukull, Walter
ABSTRACT: Background: Alzheimer's disease (AD) is a neurodegenerative brain disease that causes cognitive impairment and dementia. Within the US, AD is the most common form of dementia in the elderly, affecting 1 in 10 people over the age of 65. Sleep disturbance has been called a "public health epidemic" and, like depression, is a prodromal symptom of AD but may also contribute to the risk of developing AD. It was hypothesized that sleep disturbance, depression, and the apolipoprotein E (APOE) genotype increase the likelihood of AD. Methods: Utilizing data from the National Alzheimer's Coordinating Center, information from evaluations of 11, 453 cognitively asymptomatic participants was analyzed. Survival analysis was used to explore the independent relationships between depression, sleep disturbance, and APOE genotypes with eventual AD diagnosis. Cox proportional hazard models were utilized to explore the main effects and synergistic effects of psychosocial factors as moderated by APOE genotypes. Results: This study reinforced the association between APOE and AD. The hazard of developing AD was eight times higher for those with recent depression and theƐ 4 homozygote (HR = 8.15 [3.70–17.95]). AmongƐ 4 carriers with clinician-verified depression, the hazard was ten times that of the reference group (HR = 10.11 [4.43–23.09]). The hazard forƐ 4 carriers reporting sleep disturbance was almost 7 times greater than the reference group (HR = 6.79 [2.38–19.37]). Conclusion: Findings suggest that sleep disturbance, depression, and APOEƐ 4 genotype are associated with AD during follow-up evaluations among a group of initially cognitively asymptomatic participants. This study contributes to the literature base exploring an increased hazard or risk of AD due to potential modifiable risk factors as well as genetic biomarkers, such as APOE.